Experimental study of the application of a NiO/NiAl2O4 catalyst and a CaO-based synthetic sorbent on the Sorption Enhanced Reforming process. (5th January 2015) - García-Lario, Ana L.; Aznar, María; Martinez, Isabel; Grasa, Gemma S.; Murillo, Ramón
Abstract: A CaO-based synthetic sorbent and a NiO/NiAl2 O4 catalyst are synthesized and tested under Sorption Enhanced Reforming (SER) conditions in a fixed bed reactor. The effect of temperature, steam-to-methane ratio ( S / C ) and sorbent-to-catalyst proportion ( Z ) are studied. A SER based plant simulation model is implemented to evaluate if the operating conditions chosen allow for a self-sustained plant from a thermal energy consumption standpoint. The most appropriate temperature for SER test is 650 °C. At 600 °C the catalyst seems to be not sufficiently active, while at 700 °C, a longer breakthrough period results. SER equilibrium is reached even at the lowest S / C ratio of 1.6, obtaining H2 purity of 82 vol.% (dry basis). For the SER based plant simulation developed, the low S / C ratio of 1.6 allows a self-sustained plant where the energy required in the calciner for CaCO3 decomposition is supplied by burning the off-gas from the H2 purification unit. Highlights: Joint performance of a Ni-catalyst and a CaO-based synthetic sorbent was demonstrated. No interaction between the catalyst and the synthetic sorbent was observed. 650 °C was the most appropriate temperature value during the tests. Equilibrium concentrations were reached at steam/CH4 ratios as low as 1.6. A steam/CH4 = 1.6 allowed a self-sustained plant according to simulation work.